2010
DOI: 10.1007/s10570-010-9402-1
|View full text |Cite
|
Sign up to set email alerts
|

Solution states of cellulose in selected direct dissolution agents

Abstract: Properties of cellulose solutions in different direct dissolving liquids such as N-methylmorpholine-N-oxide and ionic liquids with varied cations and anions were investigated. The effects of different cations and anions of the used ionic liquids on the solution state were studied on the basis of the rheological characteristics of the resulting polymer solutions. The influence of these components is discussed in terms of zero shear viscosities, master curves with storage and loss moduli as well as complex visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…The additional use of pyridine as base and performing the reaction at 80 °C for 2 h yields higher DS values of up to 3.0. The acetylation of cellulose in imidazolium‐based ILs could also be used for direct conversion of the product to fibers by dry/wet spinning without previous isolation of the cellulose acetate formed …”
Section: Introductionmentioning
confidence: 99%
“…The additional use of pyridine as base and performing the reaction at 80 °C for 2 h yields higher DS values of up to 3.0. The acetylation of cellulose in imidazolium‐based ILs could also be used for direct conversion of the product to fibers by dry/wet spinning without previous isolation of the cellulose acetate formed …”
Section: Introductionmentioning
confidence: 99%
“…In addition, 3-alkyl-1-methyl imidazolium salt ILs incorporating acetate, propionate, and diethylphosphate anions were also used to dissolve cellulose, and the effect of cations and anions was intensively investigated [27,28]. Results showed that these ILs have a much better capability to dissolve cellulose than chloride salt ILs or conventional N-methyl-morpholine-N-oxide monohydrate solutions.…”
Section: Dissolution Of Cellulosementioning
confidence: 99%
“…Other applications relying on structured porous hydrogels, such as stationary phases for liquid chromatography [10][11][12][13], membranes or microfluid devices are other possible application ranges for highly structured cellulosic materials [14]. However, processability, and especially "printability" is strongly limited by the necessity of using an appropriate solvent to shape cellulose, as it is not melt-processable [15], and thus, the 3D printing of cellulose is mostly unexplored. To extend the application potential of cellulose hydrogels in analogy with other biopolymers, new methods need to be found that allow its 3D printing.…”
Section: Introductionmentioning
confidence: 99%